Perceptions of Long-Acting Injectable Antiretroviral Treatment Regimens in a United States Urban Academic Medical Center. (16th December 2020) - Koren, David E.; Fedkiv, Volodymyra; Zhao, Huaqing; Kludjian, Geena; Bettiker, Robert L.; Tedaldi, Ellen; Samuel, Rafik
Patient acceptance of long-acting injectable antiretroviral (LAI-ARV) HIV-1 regimens will determine uptake. Although previous literature reports high satisfaction, these data stem from clinical trials subject to selection bias. This cross-sectional survey from the HIV practices of an urban academic medical center assessed perceptions and preferences using Likert scales toward overall acceptability, proposed frequencies, injection-site reaction durations, and distribution venue. 59% of surveys were completed resulting 202 respondents. 60% were male, 72% black, and the median age was 49 (IQR 36-58). 93% reported a once daily tablet frequency, 69% reported single tablet regimens, and 59% reported missing zero doses in the prior 30 days. Patients self-categorized as likely (57%) or unlikely (43%) to accept LAI-ARV. Both decreasing frequencies between injections and durations of injection-site reactions resulted higher acceptability scores. 57% of respondents preferred receiving an injectable from their clinician's office over other potential options. These data demonstrate positive LAI-ARV acceptance potential.